Cover Picture: Indium Oxide as a Superior Catalyst for Methanol Synthesis by CO2 Hydrogenation (Angew. Chem. Int. Ed. 21/2016). Issue 21 (12th May 2016) - Martin, Oliver; Martín, Antonio J.; Mondelli, Cecilia; Mitchell, Sharon; Segawa, Takuya F.; Hauert, Roland; Drouilly, Charlotte; Curulla‐Ferré, Daniel; Pérez‐Ramírez, Javier
Abstract : It takes two to tango The production of the energy carrier and platform chemical methanol by CO2 hydrogenation is expected to become a key step in a sustainable economy but the realization of this process requires high‐performance catalysts. In their Communication onpage 6261 ff., J. Pérez‐Ramírez and co‐workers demonstrate that the synergistic interaction of In2 O3 and a ZrO2 carrier leads to a highly stable material that provides methanol in high space time yields and with almost 100 % selectivity.